Photocatalytic CO2 reduction by a mixed metal (Zr/Ti), mixed ligand metal–organic framework under visible light irradiation. Issue 26 (26th February 2015) - Lee, Yeob; Kim, Sangjun; Kang, Jeung Ku; Cohen, Seth M.
Abstract : Postsynthetic exchange (PSE) of Ti(iv ) into a Zr(iv )-based MOF enabled photocatalytic CO2 reduction to HCOOH under visible light irradiation with the aid of BNAH and TEOA. Abstract : Postsynthetic exchange (PSE) of Ti(iv ) into a Zr(iv )-based MOF enabled photocatalytic CO2 reduction to HCOOH under visible light irradiation with the aid of BNAH and TEOA. Use of a mixed-ligand strategy enhanced the photocatalytic activity of the MOF by introducing new energy levels in the band structure of the MOF.